Enhancing Democratic Attitudes in Elementary Students: The Effectiveness of the Value Clarification Technique - Hendrik Pandu Paksi; Putri Rachmadyanti; Roni Rodiyana; Fiena Saadatul Ummah (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to examine the effectiveness of the application of Value Clarification Technique (VCT) on the democratic attitudes of fourth grade students at SDN Kertajaya IV Surabaya. The method used in this research is Quasi Experimental with Nonequivalent Control Group Design. This study involved two groups of students, namely the experimental group treated using VCT and the control group treated using conventional learning. The research instrument used was a questionnaire to measure students' democratic attitudes before and after treatment. The validity of the instrument was tested through expert judgment and empirical tests, while data analysis was carried out using an independent t test after normality and homogeneity tests were met. The results showed that there was a significant difference in democratic attitudes between the experimental and control groups. The experimental group using VCT showed greater improvement in democratic attitudes than the control group. The average pre-test score of the experimental group was 66.06, which increased to 73.72 in the post-test. While in the control group the average pre-test score was 67.00 and increased slightly to 68.25 in the post-test. Data analysis using the t test showed that the t value was 2.166 with a significance of 0.035 (<0.05), indicating that the use of VCT was significantly more effective in improving students' democratic attitudes than conventional methods. This study concludes that the use of VCT in Civics learning is effective in improving the democratic attitudes of elementary school students. The implementation of VCT can help students understand and internalize democratic values better than conventional learning. Research recommendations include wider application of VCT in Civics education, training for teachers, as well as further research to examine the effectiveness of VCT in various educational contexts.